Ivabradine, atrial fibrillation and stroke: a combined meta-analysis and FAERS disproportionality analysis - Spadotto, Alberto; Fusaroli, Michele; Carelli, Maria; Nardi, Elena; Amadori, Martina; Massaro, Giulia; De Angelis, Veronica; Gatti, Milo; Ciubine, Valerio; Raschi, Emanuel; Poluzzi, Elisabetta; Diemberger, Igor (Frontiers in Pharmacology, 2025)
BackgroundPrevious RCTs and meta-analyses observed an increased occurrence of atrial fibrillation (AF) associated with ivabradine use. Nonetheless, these studies were not focused on AF diagnosis, and it remains unclear whether this observed increase is due to a direct effect of ivabradine or just an augmented AF detection. The latter mechanism could arise from a greater heart-rate differential between sinus rhythm and AF under ivabradine, potentially intensifying symptoms and prompting earlier clinical evaluation. If this hypothesis is true, an earlier diagnosis of AF, and subsequent earlier prophylaxis with anticoagulants, may result in a reduced incidence of ischemic cerebrovascular events.MethodsWe conducted a meta-analysis of the existing literature (calculating the ratio between ischemic cerebrovascular events and AF) combined with a disproportionality analysis of individual case safety reports of suspected adverse drug reactions. In the disproportionality analysis, we also included beta-blockers as a comparator group, given their dromotropic effect.ResultsFrom 555 studies screened in the meta-analysis, only three were considered eligible. The ratio between ischemic cerebrovascular events and AF with ivabradine was lower than with placebo (RR 0.74, 95% CI 0.62–0.89; p < 0.001). In the FAERS, AF was disproportionally reported with both ivabradine and beta-blockers (Information Component 0.84, 95% CI 0.43–1.14 and Information Component 0.53, 95% CI 0.44–0.60), while ischemic cerebrovascular events only with beta-blockers (Information Component 0.25, 95% CI 0.18–0.31).ConclusionOur findings raise the hypothesis that ivabradine facilitates an increased diagnosis rather than playing a direct role in causing AF. Prospective studies with continuous ECG monitoring and standardized endpoints are needed to clarify the temporal and mechanistic relationship between ivabradine, AF recognition, and cerebrovascular risk.